2016
DOI: 10.1007/s12010-016-2153-1
|View full text |Cite
|
Sign up to set email alerts
|

Elicitation of Medicinally Important Antioxidant Secondary Metabolites with Silver and Gold Nanoparticles in Callus Cultures of Prunella vulgaris L.

Abstract: Prunella vulgaris L. (P. vulgaris) is an important medicinal plant with a wide range of antiviral properties. Traditionally, it is known as self-heal because of its faster effects on wound healing. It is commonly known as a natural antiseptic due to the presence of various polyphenols. There is lack of research efforts on its propagation and production of bioactive compounds under field and in vitro conditions. In this study, the effects of different ratios (1:2, 1:3, 2:1, and 3:1) of silver (Ag) and gold (Au)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
63
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 152 publications
(70 citation statements)
references
References 45 publications
5
63
0
2
Order By: Relevance
“…Further investigation verified that a significant increase occurred in the total flavonoid content in the scions ( Figure 6A ), which suggested that graft union formation increases the content of a series of downstream antioxidant secondary metabolites by activating flavonoid biosynthesis. A number of studies have reported that a close relationship exists between the production of antioxidant secondary metabolites and callus formation (Fazal et al, 2016a,b). The accumulation of flavonoids may positively affect the grafting process by enhancing callus formation.…”
Section: Discussionmentioning
confidence: 99%
“…Further investigation verified that a significant increase occurred in the total flavonoid content in the scions ( Figure 6A ), which suggested that graft union formation increases the content of a series of downstream antioxidant secondary metabolites by activating flavonoid biosynthesis. A number of studies have reported that a close relationship exists between the production of antioxidant secondary metabolites and callus formation (Fazal et al, 2016a,b). The accumulation of flavonoids may positively affect the grafting process by enhancing callus formation.…”
Section: Discussionmentioning
confidence: 99%
“…Cell extraction was made with slight modifications in the protocol of . About 200 mg of dry sample was mixed with 0.5 mL HPLC grade methanol, each dilution was placed on a shaker, left overnight for 24 h at room temperature.…”
Section: Methodsmentioning
confidence: 99%
“…However, several strategies have been developed to enhance biosynthesis of these BAIs in plant cell cultures to make the production process cost efficient. Elicitation of BAIs with several biotic and abiotic compounds/products is a famous strategy to date .…”
Section: Introductionmentioning
confidence: 99%
“…However, the actual mechanism via which Au NPs enhance embryogenesis is still unclear and needs further investigation. Fazal et al 73 studied the effects of Au and Ag NPs individually or in combination on callus proliferation in Prunella vulgaris. The Ag (30 mg L À1 ), Ag-Au (1 : 2), and Ag-Au (2 : 1) NPs in combination with NAA (2.0 mg L À1 ) enhanced callus proliferation (100%) compared to the control (95%).…”
Section: Input Of Nanomaterials Towards Callus Induction Organogenesmentioning
confidence: 99%